2020
DOI: 10.3390/medicina56100544
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin in Combination with Vitamin C, Vitamin E, Coenzyme Q10 and Selenomethionine to Improve Liver Enzymes and Blood Lipid Profile in NAFLD Patients

Abstract: Background and Objectives: Non-Alcoholic Fatty Liver Disease (NAFLD) is an emerging cause of hepatopathy that is showing an increasing trend and where the recommendations of lifestyle modification are often not sufficient. The aim of this study is to evaluate the efficacy and tolerability profile of the association of silymarin, vitamin C, vitamin E, coenzyme Q10 and selenomethionine (Medronys epato®) by analyzing liver enzymes, along with the lipidic profile, as markers of liver function, and ultrasound resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Understanding these molecular mechanisms can provide a scientific foundation for exploring innovative therapeutic approaches, offering hope for more effective and sustainable strategies in mitigating NAFLD progression, especially in cases where conventional lifestyle changes are challenging (Drescher et al, 2019;Tarantino et al, 2019;Younossi & Henry, 2022). herence to lifestyle changes (Curcio et al, 2020;Handayani & Prijanti, 2024).…”
Section: Nafld With Non-alcohol Steatohepatitismentioning
confidence: 99%
“…Understanding these molecular mechanisms can provide a scientific foundation for exploring innovative therapeutic approaches, offering hope for more effective and sustainable strategies in mitigating NAFLD progression, especially in cases where conventional lifestyle changes are challenging (Drescher et al, 2019;Tarantino et al, 2019;Younossi & Henry, 2022). herence to lifestyle changes (Curcio et al, 2020;Handayani & Prijanti, 2024).…”
Section: Nafld With Non-alcohol Steatohepatitismentioning
confidence: 99%
“…For instance, along with the Mediterranean diet, twice-daily administration of silymarin (210 mg) for 6 months has led to significant improvement in the glycemic profile and regression of liver damage (Colletta et al, [ 111 ]). Silymarin, vitamin C, vitamin E, and coenzyme Q10 and selenomethionine (Medronys epato®) contain a capsule twice a day for 45- and 90-days treatments that has histologically improved liver function and reduced the marker enzymes of liver toxicity (ALT, AST, ALP, and GGT) and lipid markers (total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and TG) in serum of NAFLD patients (Curcio et al, [ 112 ]). In another study, treatment with silymarin (Eurosil 85®) and α -tocopherol (MEDAS SL) along with a low-calorie diet (1520 kcal) with exercise for three months significantly reduced ALT and AST activities and improved liver function in NAFLD patients (Aller et al, [ 113 ]).…”
Section: Antioxidants Used In Clinical Trial For Nafldmentioning
confidence: 99%
“…other neurological manifestations, suggesting that an tissue specific [39,[42][43][44][45][46]. For example, MitoQ, a mitochondrial-targeted CoQ 10 derivative, failed to offset neurodegeneration in PD clinical trials, but has shown unexpected promise in the periphery, as a therapeutic in treating non-alcoholic fatty liver disease [47,48].…”
Section: Checkered History Of Antioxidant Therapymentioning
confidence: 99%